SENDERIZACIÓN Y SEÑALÉTICA DEL ATRACTIVO NATURAL CERRO TIURA COMO ELEMENTO DE FACTOR TURÍSTICO DE LA PARROQUIA RURAL SANTIAGO DEL CANTÓN Y PROVINCIA DE LOJA - Torres Erreyes, Lizeth Catherine (2016)
Ecuador is considered one of the 17 countries with the greatest biodiversity is centralized, its tourism potential is in terms of culture, landscapes, historical sites and natural wealth, there are still attractive to visit destinations to prioritize road to go, many of them unknown, therefore it is necessary to mention the theme Interpretative trail and Signage whose purpose is to provide easy and efficient access to each of the destinations. Santiago has gastronomic, natural, cultural, due to its geographical location, beauty and environment, can be very attractive to visitors conditions, from this perspective, the present study aims to contribute to local tourism development of the sector through "INTERPRETIVE TRAIL AND SIGNAGE OF THE TOURISTIC NATURAL ATRACTION CERRO TIURA AS A TOURIST ELEMENTOF RURAL PARISH SANTIAGO CANTON AND PROVINCE LOJA. " The overall objective was raised; interpretive trail develop a design and signage for natural attraction "Cerro Tiura" as a tourist element of the rural parish Santiago Canton and Loja Province, to meet the study area three specific objectives were determined; Perform a tourist diagnosis of the current situation of rural parish Santiago Canton and Loja Province, Propose interpretive trail and Signage for natural attraction "Cerro Tiura" and Socialize the proposal of Interpretative trail and Signage for natural attraction "Cerro Tiura" with the involved characters through a participatory workshop. For each objective one methodology were apply, pursuant to the first specific objective analytical method, a diagnostic matrix by Carla Ricaurte, studies and research works, the inventory of tourist attractions the methodology proposed by the Ministry of Tourism was used, direct observation technique and field visits to the parish, interview technique, SWOT analysis, finally synthetic method for an orderly and clear analysis of results was developed. The methods used to implement the second specific objective; inductive and deductive allowed to study characteristics and technical aspects of signage, methodology Miguel Cifuentes for calculation of tourism carrying capacity, GPS determine location coordinates, operating tourist signs fundamental design cues, topographic maps produced in base software ArcGis, files for explanation of signage and referential budget, environmental impact matrix To fulfill the third and final specific objective Quick Method of Analysis of Participatory Planning (MARPP), developing a participatory workshop through expositions also carrying the physical record of attendees was applied. 5 The main results of the investigation; Santiago is a parish with a variety of natural and cultural but poorly exploited attractive due to the lack of initiatives on projects that allow the use of the same, therefore the proposal is focused on the implementation of interpretive trail and tourist signage, it also needs to build infrastructure tourism to achieve tourism development in this section. Signage system proposed frames the main attractions of the appeal, making it easier accessibility with sufficiently clear information. The proposal presented to those attending the socialization was accepted so that generated their interest in running it. With this information it can be concluded that the Rural Parish Santiago has potential tourist attractions, however, requires the implementation of projects to help improve its tourism and therefore the quality of life of the inhabitants who need training in workshops tourism training practices so that it can be considered as generating activity development of their community. Local government is recommended to take greater commitment to encouraging tourism and strategic alliances with appropriate entities for the effective use and sustainable way of these resources, across of strengthening the attractions.